Integrated Automated Agricultural Operations Using Multiple Technologies - Anandakumar, B (International Journal of Computer Sciences and Engineering, 2025)
This is a kind of technology is applicable to all type of farm land cultivation. This technology observe actual status of the land and its environment. Based on the observed data it enrich or improve the farmland cultivation. In this system its a combinations of IOT, Big data analytics, wireless sensor network technologies. In Indian scenario all the fertile land are cultivated into an manual farm. So, the yield of the land should be improved because all data's are observed from sensor as well as traditional knowledge. The proposed system observe the data from environment, soil, water and fertilizer. After the collection of information it will be analyzed. Based on the analysis we take a decision for cultivating the crop. It also take the traditional knowledge for analyzing the cultivation. The proposed system is working in the form of integrated environment. It work like an automated system. In the proposed system consist of the various sensor which are fixed into the fertile land. So, this sensor give the nature of the farmland. The proposed system improve the agriculture cultivation. We can apply this system into an all type of farmland. Whether the land is arid or water rich environment, it can be possible to give the good result.